The Influence of Live Streaming and Consumer Trust on Purchase Intention of Parfumoist Products in Lampung - Resty Putri Ulyanah; Roslina Roslina (International Forum of Researchers and Lecturers, 2025)
The growth of online shopping has encouraged brands to utilize live-streaming as a promotional tool to attract consumers, including Parfumoist in Lampung, which actively broadcasts product demonstrations to increase audience engagement. However, whether these broadcasts truly build trust and stimulate purchase intention remains uncertain, forming the central problem of this research. The research tried to analyze the influence of interactivity, visualization, entertainment, and professionalization during live-streaming on consumer trust and purchase intention. Using Stimulus-Organism-Response framework, live-streaming elements are positioned as stimuli, trust as the organism, and purchase intention as the response. A quantitative approach was employed, with purposive sampling of viewers who watched Parfumoist live streams and had made or intended to make a purchase. Data from an online questionnaire then analyzed with SEM-PLS. The findings reveal all four dimensions of live-streaming significantly affect purchase intention, mediated through consumer trust. The findings highlight that effective live-streaming depends not only on frequent broadcasts, but also on the ability of the host to interact meaningfully, present attractive visuals, entertain viewers, and display professionalism. This study concludes that improving the overall quality of live-stream sessions strengthens trust and intention to buy, offering theoretical implications for digital marketing research and practical recommendations for MSMEs to optimize live-streaming strategies in competitive markets.